Echelle gratings tiling method based on lateral shearing interferometry. (January 2022) - Li, Yifan; Mi, Xiaotao; Qi, Xiangdong; Zhang, Shanwen; Yang, Guojun; Yu, Hongzhu; Li, Xiaotian; Li, Wenhao
Highlights: The special condition in grating tiling caused by characteristics of echelles is discussed. Lateral shearing interferometry technique for dual-beam is modified for grating tiling. Theoretical analysis and simulations of the LSI method is proposed. High alignment accuracy is achieved in verification experiment using a simple setup. Abstract: A method for echelle gratings tiling based on lateral shearing interferometry is proposed. Fringe patterns of the grating assembly are generated by a wedge plate. Mosaic errors can be calculated and corrected by observing the working order and its adjacent order. An experimental mosaic of two 50 mm × 50 mm, 79 grooves / mm echelles is aligned to verify the theory. The rms wavefront is better than 0.04 wavelength. Angular and translation sensitivities of less than 1 arcsec and 10 nm are achieved respectively.